KEWENANGAN PELIBATAN ANAK SEKOLAH DALAM PROGRAM BARAK MILITER DI JAWA BARAT: The Authority to Involve School Children in Military Barracks Programs in West Java - Idul Fitra Hazman; Eko Primananda (Reformasi Hukum Trisakti, 2026)
Indonesia, as a state governed by the rule of law, places the principle of legality as a fundamental basis for all governmental actions, including those undertaken at the regional level. Every policy issued by a regional head must have a clear legal basis and comply with the prevailing laws and regulations. In 2025, the Governor of West Java adopted a policy involving school children in a military barracks program as an effort to foster discipline and character development. The research problem addressed in this study is whether the authority to involve school children in a military barracks program is in accordance with the scope of regional governmental authority granted by law. This research employs a normative legal research method, using statutory and conceptual approaches. The findings indicate that the Governor’s authority in the field of education is limited to administrative management and the supervision of secondary education and does not extend to the implementation of militaristic disciplinary programs. Furthermore, the military barracks policy potentially conflicts with the principles of child protection and the best interests of the child. Therefore, from a legal perspective, the policy raises issues concerning its validity and requires reconsideration to ensure conformity with the principle of legality and the protection of children’s rights.